2021
DOI: 10.33215/sjom.v4i2.579
|View full text |Cite
|
Sign up to set email alerts
|

Role of Knowledge Creation and Absorptive Capacity: A Panel Data Study of Innovation

Abstract: Purpose- Knowledge creation refers to the ability of firms to create new knowledge that starts from individuals to integrating the firms and then the overall economy. This study suggests that knowledge acquisition in a country has a significant relationship with innovative performance. Design/Methodology- Data from 48 highly HDI countries is taken from World Bank and World Economic Forum. Based on 480 country-year observations in a panel mediator model, it is revealed that the national efforts of boosting know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
(86 reference statements)
2
1
0
Order By: Relevance
“…Additionally, this research demonstrates a substantial positive association between knowledge-based leadership and service innovation, implying that knowledge-based leadership improves organizational performance. Finally, this analysis confirms the path-goal paradigm that KOL enhances SI by enhancing by introducing new services in the knowledge-intensive industry (Hameed et al ., 2021), which will certainly affect a university's ranking, academic efficacy, research efficiency, student satisfaction and quality development (Rehman and Iqbal, 2020; Sahibzada et al ., 2021b). This will improve organizational performance and the sustainable competitive advantage of Chinese HEIs.…”
Section: Discussionsupporting
confidence: 80%
“…Additionally, this research demonstrates a substantial positive association between knowledge-based leadership and service innovation, implying that knowledge-based leadership improves organizational performance. Finally, this analysis confirms the path-goal paradigm that KOL enhances SI by enhancing by introducing new services in the knowledge-intensive industry (Hameed et al ., 2021), which will certainly affect a university's ranking, academic efficacy, research efficiency, student satisfaction and quality development (Rehman and Iqbal, 2020; Sahibzada et al ., 2021b). This will improve organizational performance and the sustainable competitive advantage of Chinese HEIs.…”
Section: Discussionsupporting
confidence: 80%
“…By bringing together diferent ideas, concepts, and perspectives, organizations can create novel combinations that often lead to innovative solutions and stimulate creativity. Our fnding is the case in similar studies like Hameed et al [51], Liu et al [9], Asurakkody and Kim [52], and Motaghi et al [53]. Tese studies found that absorptive capacity is a critical determinant for nurses' creative and innovative behavior.…”
Section: Organizational Absorptive Capacity and Nurses'supporting
confidence: 64%
“…Furthermore, the current investigation highlights a positive and significant connection between knowledge-oriented leadership and digital orientation, suggesting that KOL can enhance the performance of knowledge workers. Finally, the analysis of this examination affirmed PGT, suggesting that knowledge-oriented leadership promotes DO by boosting the introduction of novel services in knowledge-driven industries (Hameed et al ., 2021) which, in turn, can have a considerable effect on the ranking and growth of universities, academic efficiency, research efficacy, quality development, workers and student satisfaction (Rehman and Iqbal, 2020; Sahibzada et al ., 2020c, 2023a). This will enhance the KWP and SCA in Higher Educational Institutions of China.…”
Section: Discussionmentioning
confidence: 61%